Variables Associated With Negotiation Effectiveness: The Role of Mindfulness - Pérez-Yus, María C.; Ayllón-Negrillo, Ester; Delsignore, Gabriela; Magallón-Botaya, Rosa; Aguilar-Latorre, Alejandra; Oliván Blázquez, Bárbara (Frontiers in Psychology, 2020)
Negotiation is the main mean of conflict resolution. Despite its capital importance, little is known about influencing variables or effective interventions. Mindfulness has shown to improve subjects’ performance in different settings but until now, no study has shown its impact in negotiation. The aim of this study is to analyze which variables are associated with effectiveness and to determine if meditators are more effective in negotiation. A cross-sectional descriptive study was carried out. The study variables were: socio-demographic variables, Negotiation Effectiveness (Negotiation Effectiveness Questionnaire), mindfulness (Five Facets of Mindfulness Questionnaire), emotional intelligence (Trait Meta-Mood Scale Questionnaire), Personality (NEO-FFI personality inventory), motivation (McClelland Questionnaire) and negotiation style (Rahim Organizational Conflict Inventory-II). A correlational study and a multivariate model were developed. Negotiation effectiveness was associated with age, mindfulness, emotional intelligence, extraversion, openness, conscientiousness, achievement motivation, integrating, dominating and compromising negotiation styles and inversely correlated towards neuroticism. The effectiveness of the negotiation is explained by the variables clarity, age, conscientiousness, dominating and compromising style. Meditators were found to be more effective than non-meditators.